A REVIEW OF CURRENTLY USED ISOLATED DC-DC CONVERTERS - Dobrzański, Damian (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
This paper presents a review of the most popular isolated DC/DC converters topologies. Presented solutions are divided to two main groups. First- unidirectional soft switched isolated DC/DC converters and the second one- bidirectional soft switched isolated DC/DC converters. It introduced also a two main DC/DC converters control methods. The collected results of research, simulations and tests of individual solutions carried out with different assumptions allowed for the preparation of a summary. The formulated conclusions can define the direction of development of resonant converters and a specific starting point for further research on control algorithms as well as improving the efficiency of DC converters.